A novel reduced-switch multi-level inverter based multi-device universal power-quality conditioner for PQ enhancement - Rao, Naarisetti Srinivasa; Ramana Rao, Pulipaka Venkata (International Journal of Advances in Applied Sciences, 2024)
The reduced-switch multilevel inverter (RSMLI) has garnered significant attention across various industries as a viable alternative to conventional multilevel inverter (MLI) topologies. In the realm of medium voltage high-power applications, the topologies of resonant switched MLIs are regarded as advanced due to their development with a reduced number of switching elements. The primary emphasis of the customizable multi-device universal power-quality conditioner (MD-UPQC) device is on the design and development of a significant RSMLI topology to improve power-quality (PQ) features. This study presents the development of a novel 5-level RSMLI-based MD-UPQC device, designed specifically for addressing power-quality concerns in multi-feeder distribution networks. The device facilitates uninterrupted power flow between the feeders, thereby mitigating power-quality issues. The 5-level RSMLI topology possesses the capability to decrease the necessity for a larger quantity of gate-drive circuits by implementing a switching-logic design utilizing the reduced-carrier-based pulse width modulation (PWM) technique. The 5-level RSMLI-MDUPQC device incorporates a unified voltage-current reference (UVCR) control scheme to ensure efficient operation. The functionality and efficacy of the proposed RSMLI-MDUPQC device have been assessed using the MATLAB/Simulink software tool, with the evaluation conducted under different PQ conditions. The simulation outcomes are presented for analysis and interpretation.